SCHOLAR, TEACHER, PATRIOT, INTERNATIONALIST (to the 90th birthday anniversary of the Professor K.K. Ramazanova) - Sihsaidov, A R; Gasanov, M R (History, Archeology and Ethnography of the Caucasus, 2015)
-